CITOREK TRADITIONAL LEADERSHIP AS STUDY MATERIAL IN LEADERSHIP DEVELOPMENT IN PRIMARY SCHOOLS - Oktania, Sella; Hermansah; Ila Rosmilawati (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2024)
This research aims to examine Citorek traditional leadership and its relevance in leadership development in elementary schools. Citorek traditional leadership, which is based on local wisdom and traditional value systems, has the potential to provide inspiration for the development of leadership skills based on the values of togetherness, mutual cooperation and social responsibility. The research was carried out in Citorek village, Lebak Regency. The research method used was a qualitative study with an ethnographic approach. The research subjects in this research are traditional leaders, Jaro, and the Citorek community. Data collection techniques are through in-depth interviews with traditional leaders and the Citorek community as well as direct observation. The research results show that Citorek's leadership values, such as participatory decision making and collective responsibility, are very relevant to be applied in elementary school management. In conclusion, Citorek traditional leadership can be a source of learning for elementary school principals in creating a school climate that is inclusive, participatory and based on social values